TINJAUAN NU TERHADAP TALAK DILIHAT DARI PERSPEKTIF HADITS ABGHADH AL-HALAL ILALLAHI AT-THALAQ (STUDI KASUS DI PC NU KOTA MALANG - Dina Khalidah; Ahmad Subekti; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
Success in fostering the desired goal household for every married couple. However in living life certainly will not be separated from problems. If love and harmony cannot be realized again, then Islam offers divorce as a final solution, but basically divorce is a lawful act but is hated by Allah SWT. There are more and more cases of cracks in the household that lead to divorce, especially among the Indonesian Muslim community, then this becomes an excuse to study and deepen the meaning of the hadith abghad al-halal ilallahi at-thalaq, and to find out how NU views divorce when viewed from the perspective of the hadith. This research was conducted at the PCNU office in Malang city, to find out how the views of NU as the most influential Islamic community organization regarding of divorce, especially when viewed from the perspective of the hadith abghadh al-halal ilallahi at-thalaq, as well as knowing what impacts will occur to those who experience the divorce. Then the method used in this activity is qualitative research and descriptive method. And the result of the research are a contribution of thought to the law of divorce in marriage which often occurs in social life. As for this hadith, it is included in the category of the famous ahad hadith. Keywords: Abghadh, Halal, Divorce and NU